2022
DOI: 10.1177/10778012221104844
|View full text |Cite
|
Sign up to set email alerts
|

Men Have Gender and Women Are People: A Structural Approach to Gender and Violence

Abstract: The relationship between violence and patriarchal gender systems is structural and coconstitutive; yet structural analyses that account for gender in explanations and conceptualizations of violence are often absent from violence scholarship. Additionally, there are numerous underassessed areas in more gender-nuanced, “gender-based” violence paradigms. We address the shortcomings of both types of research and propose a cohesive theoretical framework that captures the ways in which violence is patriarchy-enhanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 61 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…The association of GBV or IPV with a particular person description does not hold since this paper exposes cases of IPV perpetrators who should be the ones protecting people against it and also not being abusive. This, however, is the exception that men cause most GBV and IPV (Applin et al, 2023). The perpetrators in this paper are widely different in terms of their professions and home backgrounds.…”
Section: Discussionmentioning
confidence: 88%
“…The association of GBV or IPV with a particular person description does not hold since this paper exposes cases of IPV perpetrators who should be the ones protecting people against it and also not being abusive. This, however, is the exception that men cause most GBV and IPV (Applin et al, 2023). The perpetrators in this paper are widely different in terms of their professions and home backgrounds.…”
Section: Discussionmentioning
confidence: 88%
“…Feminist scholarship on violence against women, domestic abuse, and intimate partner violence has long demonstrated that violence is both “patriarchy-facilitated” and “patriarchy-enhancing” (Applin, Simpson and Curtis 2022). A central concern has been to foreground women’s experiences of men’s intrusions (e.g.…”
Section: Experience In Research On Partner-violent Menmentioning
confidence: 99%